NUMERICAL SIMULATION OF RETROFITTING WITH EXPANSION IN SUPPORT REINFORCE CONCRETE BEAM - Purba, Luki Hariando; Simanjuntak, Salomo; Supriyadi, Bambang (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
Beam-strengthening innovations need to be developed considering the frequent occurrence of earthquakes in Indonesia to avoid structural failure. One of the innovations in strengthening existing beams is strengthening by expanding the beam support area. This research aims to determine the behavior of strengthening existing beams. The research methods used are theoretical analysis and finite element analysis. Theoretical analysis and FEA show that strengthening the P1 beam can increase the bending and shear moment capacity by more than 50%. FEA analysis shows that retrofitting of the P1 beam increases stiffness by 45%. Strengthening the P1 beam is also able to avoid failure at the beam-column connection.